Plant Morphology and Function, Geometric Morphometrics, and Modelling: Decoding the Mathematical Secrets of Plants - Gao, Jie; Huang, Weiwei; Gielis, Johan; Shi, Peijian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Explore the fascinating world of plant functional traits in our upcoming Reprint sourced from the Special Issue in Plants. Delve into the diverse aspects of plant morphology, their responses to global climate change, and the spatiotemporal dynamics of forest productivity. Join us on a journey through the intricate web of plant characteristics and their impact on the environment.